Legal Responsibility of Marketplaces for Consumer Losses Due to Counterfeit Products: A Comparative Study of Indonesia and Singapore - Purnama, Ikmal Ramdhan; Purnama, Akmal Ramdhan; Hardiansyah, Reza; Rahman, Alip; Dimyati, Agus (International Journal of Social Service and Research, 2025)
The rapid development of e-commerce in Southeast Asia, particularly in Indonesia and Singapore, has opened up new economic opportunities, but it has also raised serious concerns regarding the circulation of counterfeit products on digital marketplace platforms. Counterfeit products not only harm the original manufacturer economically, but also endanger consumers in terms of health and safety. This research aims to evaluate and compare the legal responsibility of marketplaces for consumer losses due to counterfeit products based on regulations in Indonesia and Singapore. The method employed was a normative, juridical, and macro-comparative approach, involving the analysis of laws and regulations, legal doctrines, and interviews with stakeholders in the consumer protection sector. The results indicate that Indonesia lacks a robust legal framework for holding marketplaces accountable, which hinders consumers' access to effective legal protection. In contrast, Singapore has developed a progressive legal system through the Consumer Protection (Fair Trading) Act, which requires marketplaces to apply the precautionary principle and provide efficient dispute resolution mechanisms. The findings confirm that marketplaces should be positioned as active business actors who can be held legally liable when harm occurs to consumers due to the sale of counterfeit products. This research recommends revisions to Indonesia's Consumer Protection Law and Government Regulation No. 80/2019 to align with the development of modern e-commerce practices, including the implementation of digital product certification and reverse proof to ensure fairness for consumers.